2023
DOI: 10.1161/atvbaha.122.318559
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Preconditioned Bone Marrow Mesenchymal Stem Cells Improved Cerebral Collateral Circulation and Stroke Outcome in Mice

Abstract: BACKGROUND: Adequate collateral circulation can remarkably improve patient prognoses for patients experiencing ischemic stroke. Hypoxic preconditioning enhances the regenerative properties of bone marrow mesenchymal stem cells (BMSCs). Rabep2 (RAB GTPase binding effector protein 2) is a key protein in collateral remodeling. We investigated whether BMSCs and hypoxia-preconditioned BMSCs (H-BMSCs) augment collateral circulation poststroke, particularly through Rabep2 regulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“… 53 , 54 Transplanted stem cells can induce angiogenesis by releasing vascular endothelial growth factor, eliciting anti-inflammatory responses and other benefits. 55 The comprehensive array of ways NSCs operate in managing ischemic stroke indicates that the restoration and healing of neural networks in the brain following such an event are facilitated through various means. Because of the low survival rate of transplanted stem cells, stem cell therapy acts primarily through time-limited paracrine mechanisms.…”
Section: How Effective Is Neural Stem Cell Therapy For Ischemic Strokementioning
confidence: 99%
“… 53 , 54 Transplanted stem cells can induce angiogenesis by releasing vascular endothelial growth factor, eliciting anti-inflammatory responses and other benefits. 55 The comprehensive array of ways NSCs operate in managing ischemic stroke indicates that the restoration and healing of neural networks in the brain following such an event are facilitated through various means. Because of the low survival rate of transplanted stem cells, stem cell therapy acts primarily through time-limited paracrine mechanisms.…”
Section: How Effective Is Neural Stem Cell Therapy For Ischemic Strokementioning
confidence: 99%
“…It is known that normobaric hypoxia activates synthetic and proliferative activity in cells [103], and a number of recent experimental studies have shown that hypoxic preconditioning enhances the proliferative activity of mesenchymal stem cells [104,105], as well as neural stem cells [106].…”
Section: Proliferative and Synthetic Activitymentioning
confidence: 99%
“…Both in vivo and in vitro experiments have demonstrated that MSCs regulate the pathological processes of ischemic stroke via multiple targets. Several studies showed that MSCs enhanced collateral circulation by upregulating proteins involved in collateral remodeling and rescued damaged neurons by mitochondrial transfer and immunomodulatory effect [69,70]. MSCs are also known to facilitate axon regeneration via modulating the functioning of astrocytes and microglia [71].…”
Section: Mesenchymal Stem Cells and Ischemic Strokementioning
confidence: 99%